Produção e qualidade de melão rendilhado sob diferentes substratos em cultivo protegido - Melo, Danilo Mesquita [UNESP]; Castoldi, Renata [UNESP]; Charlo, Hamilton César de Oliveira; Galatti, Francine de Souza [UNESP]; Braz, Leila Trevisan [UNESP] (My University, 2012)
This paper aimed to evaluate the performance of hybrids of muskmelon on different substrates. Five substrates were evaluated: S 1 = coconut husk fiber, S 2 = sand; S 3 = 1/2 sand and 1/2 crushed of sugarcane, S 4 = 1/2 sand and 1/2 of peanut shell, and S 5 = I sand, I of crushed sugarcane and I of peanut shell and four hybrids of muskmelon (Bonus N°. 2, Louis, Fantasy Jab and 2007 # 16). The plants were cultivated in plastic pots of 13 dm3, which were filled with these substrates; they were arranged in plants spacing of 1,0 × 0,5 m between plants. The Fertirrigation was done by dripping, using a nutrient solution for the culture. The experimental design was a randomized blocks, in a 5 X 4 factorial design with four replications. The characteristics evaluated were: total production, average transverse and longitudinal diameter of fruit, fruit shape index; mesocarp thickness; average transverse and longitudinal diameter of the locule; index format locule; mass of fresh fruit; soluble solids, pH; titratable acidity; C vitamin; firmness of flesh; tracery of shell; and maturation index. The optimal substrate for muskmelon cultivation is a combination of 50% sand + 50% peanut shell. The hybrid Fantasy performed better compared to other hybrids.
Production and quality of muskmelon plants grown in different substrates at protected cultivation
Keywords: Coconut fiber; Crushed sugarcane; Cucumis melo; Peanut shell; Protected cultivation